The prevalence and distribution pattern of hypodontia among orthodontic patients in Southern Iran - Hedayati, Zohreh; Dashlibrun, Yunes Nazari (European Journal of Dentistry, 2013)
Objectives: To evaluate the pattern and prevalence of hypodontia and its association with different malocclusions among orthodontic patients in southern Iran. Materials and Methods: In this study, a total of 494 records of orthodontic patients (162 males, 332 females) were evaluated. To investigate percent of hypodontia pertinent information of patients was evaluated. Chi-square and Fisher′s exact tests were used for statistical analysis. Results: The prevalence of tooth agenesis was 7.66%. Thirty-eight patients were found to have at least one tooth missing. Number of patients having hypodontia was the most in class III patients, whereas the number of missing teeth was more in class II sample. However, it was not statistically significant (p = 0.569). Upper lateral incisor (27.95%), lower second premolar (21.51%), and upper first premolar (12.9%) were respectively the most frequently absent teeth. There was not statistically significant difference between sexes (p = 0.580). Hypodontia observed to be more bilaterally, in the upper arch and in the left side. Conclusion: The pattern and prevalence of hypodontia is different among races and ethnic groups. In our study population, hypodontia was found to be 7.66%. Higher prevalence of hypodontia in the maxillary arch and in class III patients may be considered as an etiologic factor.
Keywords: Hypodontia; malocclusion; orthodontics; tooth agenesis